INOVASI PENGELOLAAN PROGRAM LITERASI MELALUI KEMITRAAN PENDIDIKAN DI SD NEGERI SAGENA KECAMATAN POTO TANO - Subki, S; Rahayu, Sri (Fakultas Ekonomi dan Manajemen, 2025)
This study aims to describe and analyze the management of literacy programs through educational partnerships at SDN Sagena. The research focus includes school policies, program innovations, the roles of stakeholders, as well as the impacts and challenges in literacy implementation. The research methodology employs a Mixed Methods approach, consisting of quantitative research with a quasi-experimental design and inferential analysis using the independent samples t-test to compare learning outcomes between the group receiving the literacy program treatment and the conventional learning group. For the qualitative component, data were collected through participant observation, in-depth interviews with the principal and teachers, and documentation studies. The results show that SDN Sagena has successfully integrated the literacy program into school policy through innovative programs named